129k views
3 votes
Rearrange the equation so b is the independent variable 4a+b=−52

User Amad
by
6.0k points

2 Answers

7 votes

Answer:

b=-4a-52 or -b=4a+52

Explanation:

because you can subtract 4a to the other side or you can subtract 52 to the other side then subtract b to get the second equation.

hope this helps :)

User Basu
by
5.1k points
2 votes

The independent variable is the variable you change.

The dependent variable is the variable you measure that depends on the independent variable.

Since b is the independent variable, you need to isolate/get the variable "a" by itself in the equation: [this is because "b" is the variable you change, and "a" is the variable you measure that results/depends on "b"]

4a + b = -52 Subtract b on both sides

4a + b - b = -52 - b

4a = -52 - b Divide 4 on both sides to get "a" by itself


(4a)/(4) =(-52-b)/(4)


a=-13-(b)/(4)

User PhantomSpooks
by
5.9k points